Đánh giá chính xác chuẩn của ma trận nghịch đảo trong hệ phương trình xác định Spline loại IV - Lai, Hoang Van (Journal of Computer Science and Cybernetics, 2018)
Consider here the ease of interpolating spline S(x) for function f(x) at the points x0, x1,…,xm one has to use the conditions of continuity of S’’’(x) at the points x1, xm-1. For Spline of this type the exact bounds of inverse matrix are obtained by using the technique of three diagonal systems.